Open government in public libraries: strategic planning and public value - Voutssás Lara, Jennifer Alejandra (2016)
Information has changed in diferent ways throught ICT in the last years. Although the society itself constantly changes into new models of social relationshps under the influence of these innovations. With these changes, public institutions had to replan their work in regard of the supply of services for the citizens. A resent model was taken from practices of private corporations in management and has been transfered to the public sector for a better performance for the citizens. These research pretends to give a conceptual overview of Open Government, the concepts of strategic planning and public value and how these model has been implemented in public libraries, who help primarily to exercise the right of information, but also they allow to excercise other fundamental rights. In this research,   methodology was used throught the analisys of direct resources of international and particulary information about open government, strategic planning and public value as concepts; some cases in United States about how open government is used in public libraries; and also the analisys of indirect resources to exemplify how the strategic planning and public value has been implemented in some public libraries on México, in order to understand how Open Goverment works in these public places. New proposals are given too for future public libraries.